The Attenuation Characteristics of the Body Tissue on Frequency Function in WBAN Channel - Achmad Mauludiyanto; Gamantyo Hendrantoro; Muhammad Fachry Nova (JAREE (Journal on Advanced Research in Electrical Engineering), 2021)
The Wireless Body Area Network (WBAN) refers to a communication network between sensors placed on the inside, on the surface, or around the body wirelessly. WBAN system cannot be separated from body tissues. Body tissues also have electrical properties depending on frequency. Therefore, body tissue can affect the phenomena occurring in radio wave propagation in the WBAN channel. One of the phenomena is attenuation. This study investigates the impacts of body tissue on the WBAN channel and the effects of frequency on the attenuation of body tissue in the WBAN channel. The measurement of magnitude response was carried out with the human body as the measurement object by utilizing the S21 parameter measurement with a vector network analyzer. In NLOS conditions, a human body was located between two coplanar Vivaldi antenna. Measurements were conducted on the head, chest, and abdomen. The frequency used was in the range of 2 GHz to 6 GHz. The body tissue attenuation was obtained by finding the difference between the magnitude measurement response on the LOS and NLOS conditions. The attenuation data were analyzed using statistical and numerical analysis to determine the effect of frequency on the attenuation of the human body tissues. Based on the analysis results, it was identified that the frequency affected the human body tissue attenuation. The enhancement attenuation of the human body tissues occurred when the frequency was higher. Moreover, there was a significant difference in the body tissue attenuation in different parts of the body.Keywords: attenuation, body tissues, s-parameters, wireless body area network.